In Vitro and in Vivo antioxidant activity of ethyl acetate extraction of purple rice - Shen, Y; Chen, L; Zhang, H; Zhang, Y; Zhang, H; Wang, L; Qian, H; Qi, X; Zhang, H (Cellular and Molecular Biology, 2016)
The antioxidant activities of ethyl acetate extraction of purple rice (EAEPR) were evaluated by various methods in vitro and in vivo. In in vitro antioxidant assays, EAEPR was found to have strong 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity hydroxyl radical, reducing power and metal-ion chelating activity. In in vivo antioxidant assays, mice were administered with EAEPR via gavage for 42 consecutive days. As a result, administration of EAEPR significantly enhanced the activities of glutathione peroxidase in serums and livers of mice. EAEPR could improve the lipid status, especially total cholesterol and low-density lipoprotein cholesterol levels. In addition, total phenolic content of EAEPR was 188.21mg/g. The main phenolic compounds in EAEPR analyzed by ultra-high performance liquid chromatography tandem mass spectrometry were determined as ferulic acid and quercetin. The contents of ferulic acid and quercetin in EAEPR were 14.21mg/g and 35.28mg/g, respectively. The Nrf2 expression was significantly elevated after administration of EAEPR.These results suggested that EAEPR had potent antioxidant activity and could be explored as a novel natural antioxidant.